185k views
6 votes
Add the two expressions.

3x + 7 and 9x−2

2 Answers

5 votes

Answer:

  • 12x + 5

Step-by-step Solution:

  • (3x + 7) + (9x − 2)

[Opening the brackets]

  • => 3x + 7 + 9x - 2

[Combining Like terms]

  • => (3x + 9x) + (7 - 2)

[Simplifying]

  • => 12x + 5

User MichaelGG
by
5.9k points
4 votes

Let's add


\\ \tt\hookrightarrow 3x+7+(9x-2)

  • Remove brackets


\\ \tt\hookrightarrow 3x+7+9x-2

Combine like variables


\\ \tt\hookrightarrow 3x+9x+7-2


\\ \tt\hookrightarrow 12x+5

User Dteoh
by
4.7k points